Pengaruh Ukuran Pemerintah dan Kapasitas Fiskal Terhadap Diskresi Akrual - Nyayu Halima Thusa’dia; Maria; Yevi Dwitayanti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This consider points to experimentally demonstrate what variables influence Gathering Tact of Nearby Government in South Sumatra Territory. The free factors in this think about are Government Measure and Financial Capacity . Whereas the subordinate variable in this ponder is Collection Caution. The test utilized within the ponder was the Money related Report of the Rule / City Territorial Government in South Sumatra Territory in 2018-2022. The information utilized in this consider were gotten from auxiliary information distributed by the Preeminent Review Office and the Central Bureau of Insights. The explanatory apparatus to be utilized is Numerous Straight Relapse examination utilizing the Eviews Adaptation 12 program. The comes about in this ponder show that government measure have a positive impact on collection tact, whereas financial capacity have no impact on collection tact.